On the Historical Background of the Sefîre Treaty - Zadok, Ran
lecture at the 22nd Deutscher Orientalistentag, Tübingen 22. 3. 1983; Brg’yh king of Ktk Assyrian governor; katku Human equivalent of Akk. mātu?